Organization of the Post-Penitentiary Patronage in the Russian Empire in the XIXth - Early XXth Century - Viktoriya Stremetska (Pedagogical Discourse, 2014)
The article deals with the organization of the process of the post-penitentiary patronage in the Russian Empire in the nineteenth - early twentieth century. The process of evolution from prison charity (a care about the state of prisons in general) to patronage societies (a support of ex-prisoners) is traced. The activity of patronage societies, including types of their work, the number of wards is analyzed. It is revealed that among the types of assistance provision clothing and footwearing, a financial aid, an employment, putting children of prisoners into the shelters, etc. were prevailed. The societies engaged released persons after serving the sentence (after the first sentence, and repeated offenders), parole and probation people, and their families; adults and juveniles of both sexes. Attention is paid to analysis of a legal basis, difficulties in the functioning of societies of patronage.